2016
DOI: 10.6063/motricidade.6020
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of resistance exercise performed at different intensities on the hemodynamics of normotensive men

Abstract: The aim of this study was to investigate the acute effect of resistance exercise performed at different intensities on the hemodynamics of normotensive men. The study included 10 normotensive and recreationally-trained men (25.40 ± 6.90 years) performed the following three experimental protocols in a randomized order: a) 60% of 8RM; b) 80% of 8RM; c) 100% of 8RM. All protocols performed six exercises (Leg Press, Vertical Bench Press, Leg Flexion, Close-Grip Seated Row, Leg Extension and Shoulder Press) with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
(28 reference statements)
2
7
0
Order By: Relevance
“…Thus, we can assert that there was no PEH in this variable. A similar result was verified by Saldanha et al (2016) and Brito, Barata, Filho, and Navarro (2010) after evaluating the effect of a single training session similar to the ones of the present study. In this sense, a possible explanation can be presented due to having used trained and healthy subjects, in which many times small alterations are not observed.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, we can assert that there was no PEH in this variable. A similar result was verified by Saldanha et al (2016) and Brito, Barata, Filho, and Navarro (2010) after evaluating the effect of a single training session similar to the ones of the present study. In this sense, a possible explanation can be presented due to having used trained and healthy subjects, in which many times small alterations are not observed.…”
Section: Discussionsupporting
confidence: 77%
“…The increase in the SBP observed immediately after the P2 training (p=0.002) and P4 (p=0.032) was observed in other studies Saldanha et al, 2016) and can be explained by the increase in the chemoreceptors' activation due to peripheral fatigue (Mediano, Paravidino, Simão, Pontes, & Polito, 2005).…”
Section: Discussionmentioning
confidence: 52%
“…4,22 A high persistence of HR was identified in the PH group after the maximum load test, corroborating data presented by Saldanha (2016), who described the adjustment of the muscle afferent sympathetic activity being influenced by the accumulation of adenosine, hydrogen ions, and other metabolites, preventing the reduction of the HR to pre-exercise levels. 23 The DP behaved in a manner consistent with physical effort, increasing according to the load increment during the 1RM test and displaying significant differences only during the test ( Table 2). The increase in DP is related with increased intensity and presents higher pressure in the prehypertensive condition than normal levels.…”
Section: Discussionmentioning
confidence: 78%
“…The increase in DP is related with increased intensity and presents higher pressure in the prehypertensive condition than normal levels. 23 There was an increase in DP and SBP but no increase in cardiovascular risk according to Fornitano and Godoy (2006), who evaluated 246 volunteers and proved the predictive value of DP as a safe tool in the prescription of exercise. 24 Cornelissen and Smart (2013) demonstrated that short duration and high intensity resistance training reduces both SBP and DBP, which is also in agreement with the findings of the present study, although elevated SBP and DBP levels were observed during the experiment (Table 2) due to acute sympathetic action and posterior vagal predominance as a result of the stimulus of the 1RM test.…”
Section: Discussionmentioning
confidence: 92%
“…Taking into account the diverse methodology used for Pilates professionals, it can be seen that there is no scientific evidence on standardization of the Pilates training protocol regarding intensity, workload, the number of repetitions, recovery interval, as well as number of sets. These variables are essential factors that interfere with the cardiovascular responses and become even more critical when dealing with hypertensive patients [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%